Biometric Recognition 8th Chinese Conference, CCBR 2013, Jinan, China, November 16-17, 2013. Proceedings - Sun, Zhenan; Shan, Shiguan; Yang, Gongping; Zhou, Jie.; Wang, Yunhong; Yin, YiLong; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 8th Chinese Conference on Biometric Recognition, CCBR 2013, held in Jinan, China, in November 2013. The 57 revised full papers presented were carefully reviewed and selected from among 100 submissions. The papers address the problems in face, fingerprint, palmprint, vein biometrics, iris and ocular biometrics, behavioral biometrics and other related topics, and contribute new ideas to research and development of reliable and practical solutions for biometric authentication.
Normalization for Unconstrained Pose-Invariant 3D Face Recognition -- An Improved Adaptive weighted LTP algorithm for Face Recognition -- Robust Face Recognition Based on Spatially-Weighted Sparse Coding -- An illumination invariant face recognition scheme to Combining Normalized Structural Descriptor with Single Scale Retinex -- Shape Constraint and Multi-Feature Fusion Particle Filter For Facial Feature Point Tracking -- LPQ based Static and Dynamic Modeling of Facial Expressions in 3D Videos -- Analysis on Features and Metrics in Face Image Retrieval System -- Weight Competitive Coding for Finger-Knuckle-Print Verification -- Identification of People at a distance Using Effective Block List -- Morphological Investigations of Skulls for Sex Determination based on Sparse Principal Component Analysis.
Keywords: Computer science; Computer software; Computer graphics; Computer vision; Optical pattern recognition; Biometrics; Computer Science; Biometrics; Pattern Recognition; Image Processing and Computer Vision; Algorithm Analysis and Problem Complexity; Computer Graphics; Information Systems Applications (incl. Internet).